FORMAÇÃO DE ESTADOS QUIMERA EM DIFERENTES ACOPLAMENTOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
This work report on a study of the chimera states in networks composed by logistic maps whose interaction between them may have two types of couplings (nonlocal and power law). The Lyapunov exponents and a derivative of this quantity, the Kolmogorov-Sinai entropy, were used as analysis tool to calculate the average time of “life” or collapse time of chimera for nonlocal case with different sizes of networks. For coupling power law the results show that when it has nonlocal features it is also possible to see chimera states through the network. We also calculate the probable existence of regions of chimeras within the parameter space for both cases. Since the chimera dynamic states occurs when coexist regions that are chaotic and periodic in time, we obtained the region of the parameter space where this behavior occurs. We show the probable relations between the chimera states and the global order parameter that provides information on how the sites of a coupled network are related.
Keywords: rede; entropia; caos; Lyapunov; quimera; network; entropy; chaos; Lyapunov; chimera; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA